Analisis Pengaruh Kualitas Layanan Pembuatan Perijinan Terhadap Citra Kantor Pelayanan Perijinan Terpadu (KPPT) Kota Palembang (Kepuasan Pelanggan Sebagai Variabel Intervening) - Zein Ghozali; Munyati; Tutik Pebrianti; Indah Mawarni; Arubina Bangsawan (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2018)
This study aims to determine the effect of the quality of licensing service in the Integrated Licensing Service Office (KPPT) of Palembang City simultaneously and partially on community satisfaction and the indirect effect of the quality of licensing service on the image of the Palembang Integrated Licensing Service Office (KPPT) through community satisfaction. This research was conducted at the Integrated Licensing Service Office (KPPT) of Palembang City, with a sample of 100 service users who were taken through purposive sampling method because they were selected based on the community who took care of the SITU, SIUP and IMB permits at the Palembang City KPPT. The data analysis techniqueused is path analysis method. The results showed that simultaneous quality of licensing service at the Palembang City KPPT consisting of tangibles (X1), reliability (X2), responsiveness (X3), assurance (X4), and emphaty (X5) had a significant influence oncommunity satisfaction ( Y) at 58.2%. Partially the quality of tangibles service has a significant effect of 13%, reliability has a significant effect of 36.7%, responsiveness has a significant effect of 5.6%, assurance has a significant effect of 37.2%, and emphaty has a significant effect of 10%. Besides that, the quality of licensing service has an indirect influence on the image of KPPT Palembang City through community satisfaction, namely tangibles dimensions of 8.8%, reliability of 16.3%, responsiveness of 1.8%, assurance of 23.1%, and emphaty have an indirect effect of 7.7%. The results also showed that the image of the Integrated Licensing Service Office (KPPT) of Palembang City was positive.